2022
DOI: 10.3389/fnut.2022.883220
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Type 1 Diabetes, Persistent Symptoms, and Financial Issues Associate With Poorer Adherence to a Gluten-Free Diet in Celiac Disease After Transition From Pediatrics to Adult Care

Abstract: PurposeWe evaluated adherence to a gluten-free diet and associated factors in adult celiac disease patients diagnosed in childhood.MethodsComprehensive medical data on 955 pediatric celiac disease patients was collected and study questionnaires sent to 559 who were now adults. All variables were compared between strictly adherent and non-adherent patients.ResultsAltogether 237 adults (median age 27 years, 69% women) responded to the questionnaires a median of 18 (range 3–51) years after the childhood diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, subjects recruited via the CeD society are likely more aware of the importance of a strict GFD. In fact, we recently also observed lower adherence in a special group of adult T1D patients diagnosed with CeD in childhood ( 8 ). Taken together, despite the good GFD adherence even among the non-followed-up patients here, we consider systematic long-term surveillance particularly important in subjects with concomitant AIDs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, subjects recruited via the CeD society are likely more aware of the importance of a strict GFD. In fact, we recently also observed lower adherence in a special group of adult T1D patients diagnosed with CeD in childhood ( 8 ). Taken together, despite the good GFD adherence even among the non-followed-up patients here, we consider systematic long-term surveillance particularly important in subjects with concomitant AIDs.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, this approach remains debatable, particularly in the absence of data on the long-term prognosis of undetected CeD in AID patients. Acceptance of the treatment—strict and life-long gluten-free diet (GFD)—in these often asymptomatic individuals may also be suboptimal ( 8 ). Therefore, the current screening recommendations are inconsistent and are based primarily on the increased prevalence figures ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis performed separately in males and females confirmed the higher prevalence of psychiatric disorders in patients with altered sleep quality only among females, whereas the larger prevalence of celiac and autoimmune diseases was identified only in men with low quality of sleep. Previous studies showed that patients with celiac disease may have a variable proportion of altered sleep quality; additionally, males showed a worse adherence to gluten-free diet than females [31] and patients non-adherent to gluten-free diet have more frequently T1D [32]. Recent data also highlighted that gluten-free diet may improve sleep quality [33].…”
Section: Discussionmentioning
confidence: 99%